O paradigma sistêmico na Ciência Econômica : convergências entre Veblen, estruturas dissipativas e autopoiese - Freitas, Tales Rabelo (2015)
The debate between the paradigms of mechanical and systemic has caused important revolutions in various fields of knowledge, especially in physics, chemistry and biology. Thus, this work aims to analyze how the most recent systemic theories developed in chemistry, from Prigogine, and biology, as Maturana and Varela, can contribute to the institutional approach of Veblen. For this, will be supporting the hypothesis provided by General Systems Theory of Bertalanffy (2006), which mentions that the principles governing a given system independent of the peculiarities of its components but how these interrelate . The convergence between these three theories becomes valid once the treaty system in all type is characterized by: 1) irreversibility of the trajectory of your changes, 2) with opposition to the idea of equilibrium and 3) the introduction of a evolutionary and historical time approach. This study starts from the introduction to the debate between the paradigms of mechanical and systemic emerged in the physics branch. Following presents the theoretical frameworks of institutionalism of Veblen and the theory of dissipative structures and autopoiesis. Next up is done the analysis of convergence between visas theoretical frameworks, and verified as the approaches of Prigogine along with Maturana and Varela can contribute to the study of institutions. Finally it is shown how the approach developed in this work can assist in addressing issues related to the economy, with emphasis specifically with respect to monetary economics.